Single-ended data based fault location method for multi-branch distribution network - Zixuan Wang; Xiao Ma; Yi Lu; Chaoliang Wang; Xiangning Lin; Quan Sui (Energy Reports, 2020)
A novel single-ended travelling wave fault location method applicable to the distribution network with multi-branches is presented in this paper. The method only depends on the arrival times of the initial aerial-mode and zero-mode travelling wave, and it can solve the truncation error problem caused by discrete sampling mechanism. In addition, the method is not affected by structure of a distribution system. The feasibility and effectiveness of the presented method is verified by PSCAD/EMTDC simulation results.
Keywords: 330; Distribution network; Fault location; Improved correction algorithm; Travelling waves